If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1u + 74 = 163 Reorder the terms: 74 + -1u = 163 Solving 74 + -1u = 163 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-74' to each side of the equation. 74 + -74 + -1u = 163 + -74 Combine like terms: 74 + -74 = 0 0 + -1u = 163 + -74 -1u = 163 + -74 Combine like terms: 163 + -74 = 89 -1u = 89 Divide each side by '-1'. u = -89 Simplifying u = -89
| 4/3(x-10)=-24 | | 12m+3m=15-45 | | 6(n+9)-(1+9n)=4n | | 1/2(3-x)=21 | | -3u+3=-29 | | 5xyw=150 | | 7x^1+9x^2+9x^3= | | (2i)(9i)= | | 2x+-7=-2x+1 | | -27=5(k+2) | | 11c+6=61 | | 4x+(8)+(-5)+(-7)= | | t^4+7t^4= | | a(n-3)+8=bn(forn) | | 3x+60+(x+20)=180 | | 5+5x-4= | | X+1-1=2-1 | | x^2-11y^2=0 | | 16=2/3(2x-5) | | log(x-1)(25x)=2 | | 3x-9+4x=-12 | | log(x-1)25x=2 | | 3x+(x+20)+3x=180 | | 102=1/2(10+7) | | 9y-2=6y+1 | | 15.9n=413.4 | | 4/3(x-17)=36 | | -(-9)+2y+(-9)+6= | | 7w-3(4w+8)=7 | | X^2-6Y+2x+y^2=9 | | 23=2b+5b | | x+2x(5)+2x(2x)(10)+2x(2x)-3(25)+2x(100)+2x(500)=9382 |